A research on: factors influencing customer satisfaction among foreigners towards service provided by TMpoint Kota Bharu / Hamdi Abd Hamid - Abd Hamid, Hamdi (Faculty of Business and Management, 2010)
This research was conducted with one main objective in mind that is to identify the strategies that TMpoint can practice in order to attract more foreigners to visit TMpoint Kota Bharu. Besides, this research also tries to find the barriers that TMpoint usually face in order to attract foreigner customers come to TMpoint Kota Bharu. The data are gathered using primary and secondary data. The primary data collected using questionnaire that researcher distributes to 30 foreign customers of TMpoint Kota Bharu. Then, the researcher has categorized this study as descriptive for research design method. Next, the data gathered was analyzed by using the Statistical Package for Social Science (SPSS) Version 14. Then, all the data was interpreted and test by Frequency Distribution Analysis, Reliability Analysis, Correlations and Regression Analysis. The finding shows that all the independent variables have no association to dependent variables (customer satisfaction). Review the result from this research shows behaviors and skills of sales are the one factor that most leads to customer satisfaction. Another two factors, trust and corporate image also the factors that influence customer satisfaction that are lesser influenced. The researcher also provides some recommendations to the management to attract more foreign customers to come visit TMpoint Kota Bharu while increase more of their satisfaction. Some conclusions are provided in the research and the researcher also stated several recommendations, which are enhancing facilities, improve communication skill among employees, aggressive on promotion activities and last but not least increasing sample size that seems to influence the customer satisfaction among foreigners.